Clinical and radiological outcomes of n-HA/PA66 cages in anterior spine reconstruction following total en bloc spondylectomy for tumors - Luo, Yuanrui; Xiu, Peng; Chen, Hua; Zeng, Jiancheng; Song, Yueming; Li, Tao (Frontiers in Surgery, 2023)
Objective This retrospective monocentric study was conducted to evaluate the clinical and radiological outcomes of the nano-hydroxyapatite/polyamide66 (n-HA/PA66) cage in reconstructing the anterior column of the spine following total en bloc spondylectomy (TES). Methods A cohort of 24 patients, 20 diagnosed with primary malignant tumors and 4 with metastatic malignancies, was selected based on specific inclusion criteria. All were subjected to TES and anterior column reconstruction with the n-HA/PA66 cage from January 2013 to July 2023 at a single institution. Pre-operative embolization was performed on all patients. Documented factors included operation duration, intraoperative blood loss, length of hospital stay, treatment history, and involved level. Mechanical complications and radiological parameters such as the local kyphotic angle (LKA), anterior vertebral height (AVH), posterior vertebral height (PVH), cage subsidence, and bone fusion time were evaluated. Quality of life and neurological function were gauged using tools like the Visual Analog Scale (VAS), Eastern Cooperative Oncology Group (ECOG) performance score, Karnofsky Performance Score (KPS) scale, and American Spinal Injury Association (ASIA) grading. Results All patients were followed up for 12–127 months, with an average period of 39.71 months. An average operation time of approximately 8.57 h and a blood loss volume of about 1,384 ml were recorded. No instances of tumor recurrence or multiple organ metastases were reported, though recurrence was detected in 2 living patients. Solid fusion was achieved in all patients at a mean time of 6.76 ± 0.69 months. Cage breakage or migration was not observed. Subsidence into the adjacent vertebral bodies was identified in 3 patients but was deemed clinically irrelevant. Significant improvements in VAS, ECOG performance score, KPS scale, and ASIA scores were noted from pre- to post-surgery (P < 0.05). A marked enhancement in the AVH was observed from before surgery to immediately after (P < 0.05). LKA, AVH, and PVH values between postoperative and final follow-up showed no significant variance (P > 0.05). Conclusion The integration of TES and the n-HA/PA66 cage was found to yield promising clinical and radiological outcomes in anterior column spine reconstruction. The use of this material did not hinder oncological care, including the provision of adjuvant treatments (chemo/radiotherapy), ultimately contributing to the enhanced long-term quality of life for spinal tumor patients.